PENGARUH KECERDASAN EMOSIONAL, KECERDASAN INTELEKTUAL, DAN KECERDASAN SPIRITUAL TERHADAP TINGKAT PEMAHAMAN AKUNTANSI MAHASISWA PROGRAM STUDI AKUNTANSI DI STIE TRIATMA MULYA - Sonya Ariska Wijaya; Gde Herry Sugiarto Asana (Journal Research of Accounting, 2020)
Accounting education held in universities is intended to educate students to have competence as a professional accountant. To be able to produce qualified graduates, the tertiary institution must continue to improve the quality of its education system. The problem raised in this study is whether emotional intelligence (X1) affects the level of accounting understanding (Y) of accounting study students at STIE Triatma Mulya, whether intellectual intelligence (X2) influences the level of accounting understanding (Y) of accounting study students at STIE Triatma Mulya , whether spiritual intelligence (X3) affects the level of accounting understanding (Y) of accounting study students at STIE Triatma Mulya, what is the influence of emotional intelligence, intellectual intelligence, and spiritual intelligence on the level of accounting understanding of accounting study program students at STIE Triatma Mulya. The population in this study amounted to 146 people. This study uses the population as a sample. The data analysis technique used in this study is the instrument test, classic assumption test, F test, t test, multiple linear regression analysis, and coefficient of determination analysis. The results showed that the variables of emotional intelligence, intellectual intelligence, and spiritual intelligence partially influence the level of understanding of accounting variables.Keywords: emotional intelligence, intellectual intelligence, spiritual intelligence, level of understanding of accounting.